Techno-economic and environmental investigation of steam-exploded lignocelluloses as binder for coal-fines briquettes - Van der Westhuizen, Lodewicus (Stellenbosch : Stellenbosch University, 2025)
Van der Westhuizen, L. 2025. Techno-economic and environmental investigation of steam-exploded lignocelluloses as binder for coal-fines briquettes. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/cda9abbd-6a95-474d-b0a9-30f9f2f58bb9